Human Machine Interface with Wearable Electronics Using Biodegradable Triboelectric Films for Calligraphy Practice and Correction - Shen, Shen; Yi, Jia; Sun, Zhongda; Guo, Zihao; He, Tianyiyi; Ma, Liyun; Li, Huimin; Fu, Jiajia; Lee, Chengkuo; Wang, Zhong Lin (Nano-Micro Letters, 2022)
Letter handwriting, especially stroke correction, is of great importance for recording languages and expressing and exchanging ideas for individual behavior and the public. In this study, a biodegradable and conductive carboxymethyl chitosan-silk fibroin (CSF) film is prepared to design wearable triboelectric nanogenerator (denoted as CSF-TENG), which outputs of Voc ≈ 165 V, Isc ≈ 1.4 μA, and Qsc ≈ 72 mW cm−2. Further, in vitro biodegradation of CSF film is performed through trypsin and lysozyme. The results show that trypsin and lysozyme have stable and favorable biodegradation properties, removing 63.1% of CSF film after degrading for 11 days. Further, the CSF-TENG-based human–machine interface (HMI) is designed to promptly track writing steps and access the accuracy of letters, resulting in a straightforward communication media of human and machine. The CSF-TENG-based HMI can automatically recognize and correct three representative letters (F, H, and K), which is benefited by HMI system for data processing and analysis. The CSF-TENG-based HMI can make decisions for the next stroke, highlighting the stroke in advance by replacing it with red, which can be a candidate for calligraphy practice and correction. Finally, various demonstrations are done in real-time to achieve virtual and real-world controls including writing, vehicle movements, and healthcare. Highlights: 1 A wearable triboelectric nanogenerator (denoted as CSF-TENG) is designed using biodegradable and carboxymethyl chitosan-silk fibroin (CSF) film. 2 In vitro biodegradation of CSF film is performed through trypsin and lysozyme. 63.1% of CSF film is removed by trypsin and lysozyme after degrading for 11 days. 3 An intuitive writing system is designed by CSF-TENGs-based human-machine interface to promptly track writing steps, highlight the stroke in advance, and access the accuracy of letters.